NORTHWEST CORNER METHOD FOR NATURAL DISASTER NOTIFICATION - Hasbiyati, Ihda; Abdullah, M; Salambue, Roni; Ahriyati, Ahriyati (PATTIMURA UNIVERSITY, 2022)
Indonesia is a country that is prone to disasters such as earthquakes, floods, landslides, volcanic eruptions to whirlwinds. About 13 percent of the world's volcanoes in Indonesia has the potential to cause natural disasters with different strengths. Therefore, the government needs to take action quickly. One alternative that affects the speed of aid reaching the disaster area is transportation. In channeling natural disasters is still far from ideal, on the other hand the main object of the emergency response period is how to alleviate the burden of people affected by the disaster. So that it is needed to channel aid to every place affected by the disaster. In the distribution of assistance, constraints often occur, such as late notification and requests that do not match the supply of goods owned by the aid provider. In distributing aid to areas affected by natural disasters other than the central government, local governments have many organizations participating in it. In order to overcome these problems a system that can provide notifications and perform precise calculations is needed to find out how much assistance should be given based on existing demand and supplies. This paper discusses the optimization of the delivery of assistance through the car vehicle from the sending city of aid to the disaster area, by first determining the minimum distance from some of the sending towns to the disaster area.. The method used is the northwest corner method, MySQL, and SQLYog. The optimal solution obtained is web-based notification software in the form of SMS notifications.